1981
DOI: 10.1677/joe.0.0880401
|View full text |Cite
|
Sign up to set email alerts
|

EFFECTS OF OESTROGEN AND PROSTAGLANDIN F2α ON LUTEINIZING HORMONE RECEPTORS IN HUMAN CORPORA LUTEA

Abstract: The binding of 125I-labelled human LH (hLH) to the 2000 g subcellular fraction of human corpora lutea of the menstrual cycle was examined. Displacement studies demonstrated that 125I-labelled hLH was specifically bound in the 2000 g fraction of human luteal tissue. Specific binding of 125I-labelled hLH was demonstrated in all the corpora lutea examined except for two aged corpora lutea at an early proliferative phase of the cycle. The number of binding sites for hLH increased between the early to mid-luteal ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1984
1984
1995
1995

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…The hu man corpus luteum is LH-dependent, but continued administration of human LH does not prolong its activity significantly [10]. The administration of HCG also prolongs the life span of the corpus luteum to a certain extent, but not beyond 9 days [11], and studies on luteal cells in vitro suggest that the age of the corpus luteum is an important factor govern ing luteal cell responsiveness to gonadotro pins [12], Specific receptors for human LH and HCG have been identified in human corpus luteum by several investigators [13][14][15][16][17][18], It is well established that the number of binding sites for both hormones increases from early to mid-luteal phase and decreases towards the late luteal phase, whereas the regressing corpus luteum of the proliferative phase does not bind either hormone.…”
Section: Discussionmentioning
confidence: 99%
“…The hu man corpus luteum is LH-dependent, but continued administration of human LH does not prolong its activity significantly [10]. The administration of HCG also prolongs the life span of the corpus luteum to a certain extent, but not beyond 9 days [11], and studies on luteal cells in vitro suggest that the age of the corpus luteum is an important factor govern ing luteal cell responsiveness to gonadotro pins [12], Specific receptors for human LH and HCG have been identified in human corpus luteum by several investigators [13][14][15][16][17][18], It is well established that the number of binding sites for both hormones increases from early to mid-luteal phase and decreases towards the late luteal phase, whereas the regressing corpus luteum of the proliferative phase does not bind either hormone.…”
Section: Discussionmentioning
confidence: 99%
“…1). Molecules such as prostaglandin F2(1 (18), ovarian steroids (19) and some nucleotides (20) have been reported as affecting gonadotropin binding. 1 ) lost 70% of the inhibitory activity by heat at 90°C for 15 min, but fraction III retained all of the activity.…”
Section: Stabilitymentioning
confidence: 99%
“…The human corpus luteum is LH-dependent, but continued administration of LH does not prolong its activity [2], The admin istration of HCG also prolongs the life span of the corpus luteum to a certain extent, but not beyond 9 days [ 13], It is widely accepted that LH and HCG exert the luteotrophic effect on human corpus luteum through the specific receptors [14][15][16][17], We have reported that the number of binding sites for both hormones increases from early to mid-luteal phase and decreases towards late luteal phase [18,19], It is suggested that the ability of luteal cells to respond to LH/HCG varies during the life span of the human corpus luteum.…”
Section: Discussionmentioning
confidence: 99%